The influence of urban and mineral expansion on surface temperature variation - Santos, Arthur Pereira dos; Santil, Fernando Luiz de Paula; Carbone, Samara; Silva, Claudionor Ribeiro da (Acta Scientiarum. Technology, 2022)
This study addresses the variations in surface temperature - Land Surface Temperature (LST) - in the urban network of the municipality of Paracatu, Minas Gerais State, Brazil, which has humid tropical climate of savannah (type Aw), and in the open pit mining activity located near its urban perimeter, between the years 1990 and 2019. The area was chosen because the municipality is the most important of its microregion, being an attractive pole of work due to the presence of several companies, with emphasis on the mining company Kinross Gold Corporation, which is one of the largest open pit mines and gold producers in Brazil. Images of LANDSAT-5 and 8 satellites were used, which underwent a resampling and standardization of pixels to become the same size. The satellite choice and the period of analysis was based on the beginning of mining activity in the municipality, and a year that was able to represent its current state. Subsequently, the LST calculations made available by the United States Geological Survey (USGS) were applied. When comparing the results of both areas of the first and last year of the series, there was an increase in the variation of the mean, minimum and maximum LST, a fact that is related with the suppression of vegetation for the growth of both areas. Such suppression, together with anthropic occupation, is responsible for one of the neighborhoods (28) that present the highest average variation of LST over the years. On the other hand, the neighborhood that presented the smallest variation on this parameter (47) was recently incorporated as a neighborhood in the city´s Master Plan because it is currently being occupied by the construction of an allotment, evidencing that the temporal variability of LST in the municipality occurs in relation to anthropic presence and its magnitude.